Digital Signal Processing with Field Programmable Gate Arrays - Meyer-Baese, Uwe.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Field-Programmable Gate Arrays (FPGAs) are revolutionizing digital signal processing as novel FPGA families are replacing ASICs and PDSPs for front-end digital signal processing algorithms. So the efficient implementation of these algorithms is critical and is the main goal of this book. It starts with an overview of today's FPGA technology, devices, and tools for designing state-of-the-art DSP systems. A case study in the first chapter is the basis for more than 40 design examples throughout. The following chapters deal with computer arithmetic concepts, theory and the implementation of FIR and IIR filters, multirate digital signal processing systems, DFT and FFT algorithms, advanced algorithms with high future potential, and adaptive filters. Each chapter contains exercises. The VERILOG source code and a glossary are given in the appendices. This edition has a new chapter on microprocessors, new sections on special functions using MAC calls, intellectual property core design and arbitrary sampling rate converters, and over 100 new exercises.
Computer Arithmetic -- Finite Impulse Response (FIR) Digital Filters -- Infinite Impulse Response (IIR) Digital Filters -- Multirate Signal Processing -- Fourier Transforms -- Advanced Topics -- Adaptive Filters -- Microprocessor Design.
Keywords: Electrical engineering; Signal processing; Image processing; Speech processing systems; Computer hardware; Input-output equipment (Computers).; Electronics; Microelectronics; Communications Engineering, Networks; Signal, Image and Speech Processing; Computer Hardware; Input/Output and Data Communications; Electronics and Microelectronics, Instrumentation